Legislation Evaluation of 4/B Contracted Personnel Discipline Procedure - Baysal, Tahir (Fırat University, 2022)
Contracted personnel employment practices in administrative organizations have become widespread over the years and contracted personnel of various statuses have started to be employed. This type of employment, which was used to meet the need for impermanent, exceptional and specific service formerly, has become widespread over time and has reached a wide range of applications, from the provision of permanent and continuous services, to appointments in expert or administrator. Especially with the adoption of the New Public Management Approach, the widespread use of flexible employment in the public increased the number of contracted personnel and their weight in the total. The most comprehensive practice is the employment of contracted personnel within the scope of Article 4 / B of the Civil Servants Law No. 657. Contracted personnel employment creates many problem areas in practice as well as many innovations for the public personnel system. One of these problems is that a disciplinary legislation with standard measures and principles has not been established for contracted personnel. This situation may cause the contract personnel to lose their rights, as well as cause disruptions in the provision of public services, and the inability to apply the rules determining the working conditions. It has become a necessity to make the legal arrangements that will constitute the legal basis for disciplinary proceedings regarding contracted personnel as soon as possible.

Kamu kurum ve kuruluşlarında sözleşmeli personel istihdamı uygulamaları yıllar içerisinde yaygınlaşmış ve çeşitli statülerde sözleşmeli personel çalıştırılmaya başlanmıştır. Önceleri süreklilik arz etmeyen, istisnai ve özellikli hizmet ihtiyacını karşılamak üzere kullanılan bu istihdam türü, zaman içerisinde yaygınlaşarak daimi ve sürekli hizmetlerin gördürülmesine, uzman ya da yönetici pozisyonundaki görevlendirmelere kadar geniş bir uygulama alanına kavuşmuştur. Özellikle Yeni Kamu Yönetimi Yaklaşımının benimsenmesiyle birlikte, kamuda esnek istihdamın yaygınlaşması, sözleşmeli personel sayısını ve toplam içindeki ağırlığını artırmıştır. En kapsamlı uygulama, 657 sayılı Devlet Memurları Kanunu’nun 4/B maddesi kapsamında sözleşmeli personel istihdamıdır. Sözleşmeli personel istihdamı, kamu personel sistemi için pek çok yeniliğin yanında uygulamada çok sayıda sorun alanları da meydana getirmektedir. Bu sorunlardan biri de sözleşmeli personele yönelik olarak düzenlenmiş, standart ölçü ve ilkeleri olan bir disiplin mevzuatının oluşturulamamış olmasıdır. Bu durum, sözleşmeli personelin hak kaybına uğramasına neden olabildiği gibi kamu hizmetlerinin sunumunda aksamalara, çalışma koşullarını belirleyen kuralların uygulanamamasına da neden olabilmektedir. Sözleşmeli personele ilişkin disiplin işlemlerine yasal dayanak teşkil edecek hukuki düzenlemelerin bir an önce yapılması bir zorunluluk hâline gelmiştir.
4/B SÖZLEŞMELİ PERSONEL DİSİPLİN İŞLEMLERİNİN MEVZUAT AÇISINDAN DEĞERLENDİRİLMESİ